Respons Fisiologis Ikan Nila (Oreochromis niloticus) terhadap Perubahan Kualitas Air yang Lingkungan Ekstrem - Aminah, Aminah; Rina Iskandar (Lembaga Pengembangan Kinerja Dosen, 2026)
Extreme changes in water quality, whether in the form of temperature fluctuations, exposure to detergents, pH decreases due to acetic acid, or changes in salinity, have the potential to cause complex physiological disorders in tilapia. The research aims to analyze the physiological responses of tilapia to changes in water quality in extreme environments given exposure to Temperature, Detergent, Acetic Acid, and Salinity. This research was conducted at the Wet Laboratory of Achmad Yani University, Banjarmasin. The physiological parameters observed included fish behavior, respiratory frequency measured by the number of openings and closings of the operculum per minute, gill condition, and mucus production on the body surface. Exposure to extreme environments in the form of high temperatures, detergents, acetic acid, and salinity caused physiological disorders in tilapia with varying levels of response. Exposure to acetic acid had the most rapid and severe impact, characterized by damage to scales and fins, impaired movement to the point of fish capsizing, and unstable breathing, while detergent and temperature triggered changes in external organs, heart rate, and behavior. Salinity treatment primarily affected osmoregulatory function as seen from increased respiratory frequency and heart rate. All treatments showed that extreme changes in water quality can cause significant physiological stress in tilapia.